Effect of Pulse Rate on Loudness Discrimination in Cochlear Implant Users - Azadpour, Mahan; McKay, Colette; Svirsky, Mario (Association for Research in Otolaryngology, 2018)
Stimulation pulse rate affects current amplitude discrimination by cochlear implant (CI) users, indicated by the evidence that the JND (just noticeable difference) in current amplitude delivered by a CI electrode becomes larger at higher pulse rates. However, it is not clearly understood whether pulse rate would affect discrimination of speech intensities presented acoustically to CI processors, or what the size of this effect might be. Intensity discrimination depends on two factors: the growth of loudness with increasing sound intensity and the loudness JND (or the just noticeable loudness increment). This study evaluated the hypothesis that stimulation pulse rate affects loudness JND. This was done by measuring current amplitude JNDs in an experiment design based on signal detection theory according to which loudness discrimination is related to internal noise (which is manifested by variability in loudness percept in response to repetitions of the same physical stimulus). Current amplitude JNDs were measured for equally loud pulse trains of 500 and 3000 pps (pulses per second) by increasing the current amplitude of the target pulse train until it was perceived just louder than a same-rate or different-rate reference pulse train. The JND measures were obtained at two presentation levels. At the louder level, the current amplitude JNDs were affected by the rate of the reference pulse train in a way that was consistent with greater noise or variability in loudness perception for the higher pulse rate. The results suggest that increasing pulse rate from 500 to 3000 pps can increase loudness JND by 60 % at the upper portion of the dynamic range. This is equivalent to a 38 % reduction in the number of discriminable steps for acoustic and speech intensities.
Keywords: Cochlear implant; Stimulation pulse rate; Loudness discrimination; Loudness variability